O-201 Prenatal and postnatal outcome of mosaic embryo transfers: multicentric study of one thousand mosaic embryos diagnosed by preimplantation genetic testing with trophectoderm biopsy. (6th August 2021) - Spinella, F; Victor, A; Barnes, F; Zouves, C; Besser, A; Grifo, J A; Cheng, E H; Corti, L; Minasi, M G; Greco, E; Munné, S; Fiorentino, F; et al.
Abstract: Study question: To explore the effect of chromosomal mosaicism detected in preimplantation genetic testing (PGT-A) on prenatal and postnatal outcome of mosaic embryo pregnancies Summary answer: No significant difference between euploid and mosaic embryos was observed in terms of weeks of gestation, average weight, and developmental defect of the babies born What is known already: Mosaic embryos have the potential to implant and develop into healthy babies. Transfer of these embryos is now offered as an option for women who undergo IVF resulting in no euploid embryos. While, prenatal diagnosis has shown the depletion of chromosomal mosaicism in mosaic embryos, several concerns remain. For instance, the direct effects of different kind of mosaicism on prenatal/postnatal outcome and the possibility that intra-biopsy mosaicism in the TE is a poor predictor of the ploidy status of the ICM. Thus, there is certainly a need for comprehensive analyses of obstetrical and neonatal outcome data of transferred mosaic embryos. Study design, size, duration: Compiled analysis from multicenter data on transfers of mosaic embryos (n = 1, 000) and their outcome, with comparison to a euploid control group (n = 5, 561). To explore the effect of embryonic mosaicism on newborns, we matched mosaic embryos resulting in a birth with a euploid embryo by a series of parameters (maternal age, embryo morphology, and indication for PGT-A). Prenatal tests and birth characteristics of > 200 neonates from mosaic embryo transfers were compared to > 200 euploid embryos. Participants/materials, setting, methods: PGT-A was performed on blastocyst-stage embryos with 24-Chromosome whole genome amplification (WGA)-based Next Generation Sequencing (NGS). In accordance with established guidelines, embryos were categorized as mosaic when PGT-A results indicated 20-80% aneuploid content. Prenatal testing where performed in 30% of pregnancies with amniocentesis, 4% did an extra analysis for potential UPD for the suspected mosaic chromosome, and an additional 16% performed chorionic villus sampling (CVS) and 9.5% performed noninvasive prenatal testing (NIPT). Main results and the role of chance: Of the 465 mosaic embryos that implanted, about 20% miscarried, and out of those, 75% were early spontaneous abortions. Of the pregnancies, 3 out of 368 were stillborn (2 out of them were twins that were extremely premature at 23 weeks, and the other died during pregnancy from a heart defect). The remaining 99% of those have been born or are late ongoing pregnancies at the time of analysis. Prenatal tests were performed in > 200 pregnancies and the vast majority tested normal. All 5 abnormal cases were amniocentesis tests showing microdeletions or insertions of sizes smaller than the resolution used during PGT-A, so they were unrelated to the mosaicism detected with PGT-A. In fact, in none of the cases did the prenatal test reflect the mosaicism detected at the embryonic stage. Matching each of the 162 mosaic embryos resulting in a birth with a euploid embryo, we found that the length of gestation was similar on average, and so was the average weight of the babies at birth. We also gathered information on the routine physical examination performed on babies at birth, and of those 162 babies from mosaic embryo transfers, none had obvious developmental defects or gross abnormalities. Limitations, reasons for caution: Even though newborns resulting from mosaic embryo transfers in this study invariably appeared healthy by routine examination, concerns for long-term health cannot yet be entirely dispelled. The question must therefore be carefully considered by each clinic and patient situation. Wider implications of the findings: Prenatal testing of > 200 pregnancies from mosaic embryo transfers showed no incidence of mosaicism that matched the PGT-A findings, indicating the involvement of self-corrective mechanisms. Pregnancy and obstetric data indicates that mosaic embryos prevailing through gestation and birth have similar chromosomal and physiological health compared to euploid embryos. Trial registration number: none